Specificity and kinetics of human candidate cerebral malaria biomarkers in mice - Gomes, Cláudia; Chicas, Lizeth; Crotty, Kelly A.; Salzano, Isaac; Tawfiles, Davidi; Rodriguez, Ana (Frontiers in Malaria, 2025)
Cerebral malaria (CM) is a complication of infection with Plasmodium falciparum that can lead to cognitive sequelae and death. The diagnosis of CM is based on clinical criteria, which leads to frequent misdiagnosis as it is confused with other infections that induce coma in children. There is currently no possibility of early diagnosis of this complication, since CM is only identified after the presentation of neurological signs, which greatly decreases treatment success and also precludes the analysis of patient’s early samples for the identification of predictive/prognostic biomarkers. Here we have used the mouse model for CM (infection with Plasmodium berghei-ANKA) and compared it to a non-CM model (infection with P. berghei-NK65) to evaluate the early kinetics and specificity of two candidate biomarkers that are elevated in the plasma of patients with CM: Angiopoietin-2 and Angiopoietin-like 4. The mouse experimental CM (ECM) model allows for the study of the biomarker’s kinetics throughout infection, starting before neurological signs are evident, and for their specificity for ECM as compared to the non-cerebral model. Our results indicate that, similar to findings in P. falciparum malaria patients, Angiopoietin-2 and Angiopoietin-like-4 are significantly elevated in plasma during P. berghei infection in mice. In mice infected with P. berghei-NK65 there was a direct correlation with the levels of parasitemia, suggesting that this may be contributing to the increased levels of both candidate biomarkers during infection, however this was not observed in P. berghei-ANKA infected mice. In these mice, a high proportion developed ECM and showed elevated levels of Angiopoietin-like 4, which were not observed in mice with non-cerebral infections. Angiopoietin-like 4 levels were directly correlated with severity of ECM. This observation is similar to previous findings in human malaria patients and provide basis for the use of mice as a model to investigate early kinetics and specificity of potential biomarkers for human severe and cerebral malaria.